Engagement and understanding: pregnant adolescents and health information in Freedom Park - Stevens-Uninsky, Maya (Department of Public Health and Family Medicine, 2016)
Adolescent and young adult pregnancy is a major sexual health issue for vulnerable young women in South Africa. Beginning by examining the origins of adolescent pregnancy in South Africa, this paper then proceeds to examine the various sources of health information accessible to adolescent women, and how said information is used. Finally, it examines the disconnect between know ledge and use of health information, and the role this plays in high levels of adolescent pregnancy. This independent research examines how adolescent women in the South African township of Mitchells Plain, Cape Town (specifically the neighbourhood of Freedom Park) understand and engage with the limited health information at their disposal. Through a qualitative research process resulting in interview analysis, this article explores how vulnerable young women internalize, believe, and use health information, in order to better understand the causes of adolescent pregnancy and risky sexual behaviour. Participants were adolescent (18 -¬‐ 20) women, who were residents of Freedom Park, (a neighbourhood in Mitchells Plain) and were either pregnant or had a child. Demographic screening tools (n=31) were used to select participants for semi -¬‐ structured interviews (n=30). Interviews were later transcribed verbatim, and analyzed using NVIVO. In this Freedom Park sample, the ability of young women to internalize and act upon information about sexuality and health varied depending on who proffered that information and how those individuals were perceived by the recipient. In the research, three key factors emerged as impacting the internalization and later use of reproductive health information. First, for both sources of health information and for recipients, life experience s played a critical role in making information more relatable and therefore easier to internalize, believe and use. Second, the perceived trustworthiness of the source of information made the knowledge more believable and relevant to the recipient. Finally, high levels of comfort in discussing sexual health with the source of information made information more easily internalized, while fear of negative judgment from sources reduced comfort and discussions of sexual health. The research suggests that efforts to reduce instances of adolescent pregnancy in South Africa should pay close attention to who delivers information about health and sexuality. To be effective, young women should feel they share experiences with, trust in, and are comfort able with sources of information. Future research should pursue how improving adolescent's engagement with health information through feelings of belonging, self ‐ efficacy, and empowerment can improve understanding, trust, and utilization of health information.